UTILIZATION OF INFORMATION MEDIA IN FORMING THE IMAGE OF POLITICIANS/POLITICAL PARTIES - Khairah, Nona; Katimin, Katimin; Samosir, Hasrat Efendi (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
The use of mass media and social media has become one of the main strategies in the image of politicians and political parties in this digital era. The development of information technology, especially the internet and social media, allows political communication to take place faster, more interactively, and more accessible to various groups of society. This article aims to analyze the role of information media in shaping political image through a qualitative approach with a literature review method . This study collects, analyzes, and synthesizes various relevant literature sources, such as books, journal articles, and seminar papers, to understand how politicians and political parties use media as a tool for communication, branding , and political image. The results of the study show that mass media, although still having a significant role, is increasingly being replaced by social media which offers politicians the convenience of building personal branding and interacting directly with voters. Political image building through these two types of media not only functions to shape public perception, but also to manage public opinion and influence political decisions. Social media, in particular, provides an opportunity for politicians to build an image that is more personal and responsive to the needs of the community. This study also discusses various communication theories that explain the influence of mass media on political behavior, such as reinforcement theory , agenda setting, priming, framing , and direct effect theory .